Adaptive molecular quaternary clips made with pyrene functionalized polyhedral oligomeric silsesquioxane. Issue 1 (25th November 2020) - Yang, Tsung-Kai; Ou, Jou-Tsen; Lin, Heng-Yi; Peng, Wei-Cheng; Jao, Meng-Hsuan; Chen, Jia; Sun, Bin; Zhu, Yu; Wang, Chien-Lung
Abstract : A novel adaptive Q-clip was developed to overcome the difficulties in bulk self-assembly of unimolecular multi-clips. By pinching exclusively 4 eq. of allosteric activators, the Q-clip carries out rapid host–guest assembly in bulk. Abstract : Evolving synthetic molecules toward complex structures is a major goal in supramolecular chemistry. Increasing the number of clips in a unimolecular multi-clip (UMC), although vital to elevate the complexity of supramolecular architectures, often prevents the UMC from forming host–guest complexes in the bulk phase. To overcome this difficulty, adaptive chemistry was applied to develop a novel adaptive unimolecular quaternary clip (Q-clip ). The Q-clip is intrinsically amorphous, but self-organizes with exclusively 4 eq. of allosteric activators (NDI ) to form the Q-clip  : NDI4 complexes and a supramolecular lamellar structure in the bulk. The adaptive assembly is fast and allows us to locate the adaptive assembly area of Q-clip  : NDI4 complexes in the amorphous Q-clip film. Our results provide new insights into the design of adaptive UMCs for the evolution toward complex structures and supramolecular functional materials.